Kekuatan digital: Peran penting media digital dalam menggiring opini publik terhadap isu Palestina - Agustin, Nanda Bintang (Maliki Interdisciplinary Journal, 2024)
Throughout history, the media has played a crucial role in influencing public opinion on various social, political, and humanitarian issues. In the contemporary digital age, the power and impact of digital media in shaping public perceptions and attitudes towards global conflicts, such as the Palestine issue, have become increasingly significant. This essay explores the profound influence and importance of digital media in shaping public opinion on the Palestine issue, emphasizing the role it plays in disseminating information, mobilizing support, and influencing narratives. Digital media serves as a powerful tool for disseminating information and raising awareness about the ongoing complexities surrounding the Palestine-Israel conflict. Through various digital platforms such as social media, online news outlets, and multimedia content, information regarding the historical background, current events, and human rights violations in Palestine reaches a global audience instantaneously. By providing a platform for different perspectives and voices to be heard, digital media contributes to a more comprehensive understanding of the issue among the public. Keywords: Digital media, Public Opinion, Palestine Issue.